Aprendendo a autogestão: reconhecimento do trabalho e conflitos distributivos em uma cooperativa de catadores - Viviane da Silva Serafim (2021)
The form of remuneration for work can be conceived based on several parameters and criteria that are inherent to the trajectory of an organization or economic enterprise. Among the most classic models in the literature on remuneration processes, there is a record of capitalist, socialist, communist and Solidarity Economy experiences, which in turn demonstrate the complexity of the criteria, norms and collective agreements that are established by organizations to reach the final remuneration amount. Based on this context, the objective of this work is to investigate the elements that contributed to the establishment of the criteria for the remuneration of the pickers of Shed B of the Association of Pickers of Paper, Cardboard and Reusable Materials of Belo Horizonte (ASMARE) and understand the effects that the form of remuneration causes in the relationships of waste pickers within the association. To this end, a qualitative research was carried out under the case study method to try to understand how these elements appear within the management of Shed B and what transformations result from this process. In order to have a more in-depth analysis of the work situation, interviews and field observations were made during the workday of the pickers guided by the Ergonomic Analysis of Work (AET). Once the data were collected, they were transcribed and revised so that it was possible to carry out the self-confrontations of the information with the collectors, as proposed by the Theory of the Course of Action. Thus, this work presents a rescue of the association's trajectory and the process of formation of Shed B demonstrating how the historical process contributed to the form of remuneration practiced during the research. As a result, the advances and limits of each of the forms of remuneration already practiced by Shed are presented, and the effects that these end up affecting in the workday and in the interpersonal relationships of the collectors.